ANALISIS BREAK EVEN POINT (BEP) - Manuho, Priskila; Makalare, Zevania; Mamangkey, Trixie; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2021)
This paper aims to provide information to the public regarding the meaning, use, purpose, limitations, and methods of calculating Break Even Point Analysis (BEP). Management needs information that can be used as a basis for planning company profits. By knowing the break-even point, management can determine the amount of production or sales that must be made, according to the profit target to be achieved). Due to the Covid-19 pandemic, the data collection technique used is an online study, namely by taking references from the Internet. The type of data used is secondary data in the form of books related to the discussion, of course, books/materials on the internet. Data analysis used descriptive method, which was to describe the research results and then draw conclusions. Break Even Point (BEP) calculation can be done by equation method, contribution margin method, and graphical method. The three methods when used produce the same number. Break Even Point (BEP) analysis, in practice, besides containing benefits but also contains weaknesses.